Estimating the Cost of Administering the Department of Defense Small Business Innovation Research (SBIR) Program - Seong, Somi (RAND Corporation, 2008)
Currently, Small Business Innovation Research (SBIR) funds cannot be used to administer the SBIR program; SBIR administration must be funded from other sources. As Congress reauthorizes the program, it is considering whether to allow partial use of SBIR set-asides for SBIR program administration costs and, if so, at what levels. In this report, the authors estimate how much it currently costs to administer the DoD SBIR program.